The role of Latin American bodies to the international standard setting: who are they and what are they doing? - Lopes, A. (Standardization of Financial Reporting and Accounting in Latin American Countries, 2015)
This chapter presents an overview, on a twofold perspective, of the role of Latin American (LATAM) countries in the process of setting international standards. Firstly, at the international level, it checks who are the LATAM bodies and persons who have a seat in the structure of IFRS Foundation and the IASB’s advisory bodies, highlighting their role and the required individual skills. Secondly, at the regional and local levels, it looks at the accountancy bodies in each LATAM country, to identify what they are doing regarding the process of convergence and adoption of international accounting standards. The topics discussed conclude that (1) overall Brazil seems to assume the leading position and the most prominent role, (2) Brazil, Mexico, Argentina, and Venezuela are the most engaged with IASB’s work, and (3) Brazil and Mexico have the most diverse and available information on the activities developed by local accountancy’s bodies and respective consequences for financial reporting.